MANAJEMEN EKSTRAKURIKULER BACA TULIS AL-QUR’AN (BTA) DI SMK BINA NEGARA GUBUG GROBOGAN - RAHAYU, MAYA PUJI; MAULIDIN, SYARIF (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This study aims to analyze the planning, implementation, and evaluation of the student talent and interest development program at SMK Bina Negara Gubug. The planning process involves the formulation of extracurricular programs with the participation of several parties, including the vice-principal of student affairs, extracurricular advisors, and the school principal, focusing on activities that can enhance students' potential. The program's implementation is evaluated based on goal achievement and challenges faced, such as time constraints, student enthusiasm, and weather factors. Program evaluation is conducted periodically to assess the effectiveness and efficiency of each extracurricular activity. The results show that despite challenges, the programs successfully had a positive impact on developing students' talents and interests, with some activities receiving high enthusiasm and achieving achievements. This study recommends further development of less popular extracurricular programs and improving supporting facilities to optimize the programs in the future. The development prospects are expected to be applied to other schools by adjusting to the needs and potential of the students. ABSTRAKPenelitian ini bertujuan untuk menganalisis perencanaan, pelaksanaan, dan evaluasi program pengembangan bakat dan minat siswa di SMK Bina Negara Gubug. Perencanaan dilakukan melalui penyusunan program ekstrakurikuler yang melibatkan berbagai pihak, termasuk waka kesiswaan, guru pembina, dan kepala sekolah, dengan fokus pada kegiatan yang dapat mengembangkan potensi siswa. Pelaksanaan program dievaluasi berdasarkan pencapaian tujuan dan kendala yang dihadapi, seperti masalah waktu, antusiasme siswa, dan faktor cuaca. Evaluasi program dilakukan secara berkala untuk menilai efektivitas dan efisiensi setiap kegiatan ekstrakurikuler. Hasil penelitian menunjukkan bahwa meskipun ada tantangan, program yang telah dilaksanakan berhasil memberikan dampak positif terhadap pengembangan bakat dan minat siswa, dengan beberapa kegiatan yang mendapat respon antusiasme tinggi dan mencapai prestasi. Penelitian ini menyarankan pengembangan lebih lanjut pada program ekstrakurikuler yang kurang diminati dan memperbaiki sarana prasarana pendukung agar lebih optimal di masa depan. Prospek pengembangan ini diharapkan dapat diterapkan pada sekolah-sekolah lain dengan menyesuaikan kebutuhan dan potensi siswa yang ada.